2018
DOI: 10.1002/zaac.201800111
|View full text |Cite
|
Sign up to set email alerts
|

[A([18]crown‐6)]2[Ni(CO)3]·8NH3 (A = K, Rb) – An Ammoniate with a Trigonal Planar [Ni(CO)3]2– Anion

Abstract: The new carbonyl nickelate salt [A([18]crown‐6)]2[Ni(CO)3]·8NH3 (A = K, Rb) serendipitously crystallized from a solution of (PPh3)2Ni(CO)2, [18]crown‐6, [2.2.2]cryptand, and K6Rb6Ge17 in liquid ammonia. The [Ni(CO)3]2– anion represents the first tricarbonyl compound of nickel characterized by X‐ray diffraction studies and completes the row of known carbonyl metalates. The planar anion displays approximately D3h symmetry. The calculated electron localization function (ELF) of the complex shows plane basins abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 38 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…The latter include, for instance, the production of base chemicals [2] or materials [3] as well as applications in the areas of life science [4] and catalysis [5, 6] . Anionic TM carbonylates were discovered in 1931, [7] although the mononuclear nickelate [Ni(CO) 3 ] 2− was not structurally characterized until 2018 [8] . Compared to their anionic counterparts, transition metal carbonyl cations (TMCC) were only discovered about 30 years later, with the first reports published in 1961 [5, 9] .…”
Section: 4 5 6 7 8 9 10 11 12mentioning
confidence: 99%
“…The latter include, for instance, the production of base chemicals [2] or materials [3] as well as applications in the areas of life science [4] and catalysis [5, 6] . Anionic TM carbonylates were discovered in 1931, [7] although the mononuclear nickelate [Ni(CO) 3 ] 2− was not structurally characterized until 2018 [8] . Compared to their anionic counterparts, transition metal carbonyl cations (TMCC) were only discovered about 30 years later, with the first reports published in 1961 [5, 9] .…”
Section: 4 5 6 7 8 9 10 11 12mentioning
confidence: 99%
“…The earlier discovered nickel analogue exhibits the same structural motif. [8] Voids in the unit cell are filled by additional ammonia molecules of crystallization. While one of the ammonia molecules shows no preferred direction for the hydrogen atoms, by investigating the N -N distances, as well as the direct surroundings of the nitrogen atom, an amide or hydroxide molecular anion can be excluded.…”
Section: Crystal Structure Of [A([18]crown-6] 2 [Pt(co) 3 ] • 10 Nh 3...mentioning
confidence: 99%
“…In addition to neutral complexes, also a number of carbonyl metalate anions are known [6] . While mononuclear carbonyl metalates are known for every metal of groups 3 to 9, [7] so far only the nickelate [Ni(CO) 3 ] 2− has been discovered out of the group 10 elements [8] …”
Section: Introductionmentioning
confidence: 99%
“…For a detailed review of metal carbonyl anions, see: Ellis (2003). Only very recently, the first tricarbonyl nickelate, [Ni(CO) 3 ] 2-, could be synthesized via the reaction between Ni(CO) 2 (PPh 3 ) 2 , K 6 Rb 6 Ge 17 and chelating ligands in liquid ammonia (Lorenz et al, 2018). Thus, it was again demonstrated that Zintl phases are suitable for the reduction of metal carbonyl complexes.…”
Section: Structure Descriptionmentioning
confidence: 99%